Deadly heat - Castle, Richard (Nikki Heat series, 2013)
Determined to find justice for her mother, top NYPD Homicide Detective Nikki Heat continues to pursue the elusive former CIA station chief who ordered her execution over a decade ago. For the hunt, Nikki teams once again with her romantic partner, Pulitzer Prize-winning investigative journalist Jameson Rook. Their quest for the old spy and the motive behind the past murder unearths an alarming terror plot - which is anything but ancient history. It is lethal. It is now. And it has already entered its countdown phase.